tDCS over the primary motor cortex contralateral to the trained hand enhances cross-limb transfer in older adults - Kaminski, Elisabeth; Maudrich, Tom; Bassler, Pauline; Ordnung, Madeleine; Villringer, Arno; Ragert, Patrick (Frontiers in Aging Neuroscience, 2022)
Transferring a unimanual motor skill to the untrained hand, a phenomenon known as cross-limb transfer, was shown to deteriorate as a function of age. While transcranial direct current stimulation (tDCS) ipsilateral to the trained hand facilitated cross-limb transfer in older adults, little is known about the contribution of the contralateral hemisphere to cross-limb transfer. In the present study, we investigated whether tDCS facilitates cross-limb transfer in older adults when applied over the motor cortex (M1) contralateral to the trained hand. Furthermore, the study aimed at investigating short-term recovery of tDCS-associated cross-limb transfer. In a randomized, double-blinded, sham-controlled setting, 30 older adults (67.0 ± 4.6 years, 15 female) performed a short grooved-pegboard training using their left hand, while anodal (a-tDCS) or sham-tDCS (s-tDCS) was applied over right M1 for 20 minutes. Left (LHtrained) - and right -hand (RHuntrained) performance was tested before and after training and in three recovery measures 15, 30 and 45 minutes after training. LHtrained performance improved during both a-tDCS and s-tDCS and improvements persisted during recovery measures for at least 45 minutes. RHuntrained performance improved only following a-tDCS but not after s-tDCS and outlasted the stimulation period for at least 45 minutes. Together, these data indicate that tDCS over the M1 contralateral to the trained limb is capable of enhancing cross-limb transfer in older adults, thus showing that cross-limb transfer is mediated not only by increased bi-hemispheric activation.